Analisis Pengaruh Kualitas Produk, Brand Image dan Life Style terhadap Keputusan Pembelian Konsumen Merek Uniqlo (Studi Kasus pada Mahasiswa di Yogyakarta) - Deri Yuansyah; Ambar Lukitaningsih; Lusia Tria Hatmanti Hutami (Universitas Batanghari Jambi, 2023)
The economy in this era continues to grow and increasingly leads to very tight competition, especially in the field of business carried out by companies that produce similar goods or services. Uniqlo is a retail company that also offers fashion and lifestyle products with brands originating from Japan. This study aims to determine whether Product Quality, Brand Image, and Lifestyle influence consumer purchasing decisions at Uniqlo in Yogyakarta. The sampling method used is a non-probability method with purposive sampling technique. Collecting data by distributing questionnaires directly to 100 respondents. Data is processed using SPSS, and the analysis tool uses Multiple Linear Regression analysis. The results of the analysis of questionnaire data partially Product quality has a negative and significant effect on purchasing decisions. Partially, Brand Image has a positive and significant effect on Purchasing Decisions. Partially, Life Style has a positive and significant effect on Purchasing Decisions. Product Quality, Brand Image, Life Style, simultaneously or jointly have a positive and significant effect on purchasing decisions.